1993
DOI: 10.1099/0022-1317-74-11-2373
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the S1 and S2 subunits of murine coronavirus JHMV spike protein by a vaccinia virus transient expression system

Abstract: The spike (S) protein of murine coronavirus JHMV, variant cl-2, comprises two polypeptides, N-terminal S 1 (with an N-terminal signal peptide) and C-terminal $2 (with a C-terminal transmembrane domain). In order to express these subunits, we constructed three different vaccinia virus transfer vectors (VV-TVs) containing cDNAs encoding the S1 protein without a transmembrane domain (pSFSlutt), the S1 protein with a Cterminal transmembrane domain derived from $2 (pSFSltmd) or the $2 protein with an N-terminal sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
14
0

Year Published

1994
1994
2011
2011

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 25 publications
0
14
0
Order By: Relevance
“…The structure of the S2TM Ϫ gene suggested that the protein was smaller than the native S2 protein, since it lacked 71 C-terminal aa. It was shown in our previous work that ssS2 expressed in a vaccinia virus expression system was larger than the authentic S2 protein produced in cells infected with cl-2 virus (18).…”
mentioning
confidence: 75%
See 1 more Smart Citation
“…The structure of the S2TM Ϫ gene suggested that the protein was smaller than the native S2 protein, since it lacked 71 C-terminal aa. It was shown in our previous work that ssS2 expressed in a vaccinia virus expression system was larger than the authentic S2 protein produced in cells infected with cl-2 virus (18).…”
mentioning
confidence: 75%
“…In order to assess the receptor-binding capacity of S2, an S2 protein without the transmembrane domain and the cytoplasmic tail was prepared, since this protein was expected to be secreted in the culture fluid of cells. The gene encoding the S2 protein with a signal peptide at the N terminus and without the transmembrane domain (S2TM Ϫ ) was made by PCR from the ssS2 gene, which has signal sequence and transmembrane domain (18). With this gene as a template, two different oligonucleotide primers were constructed: the forward primer, PL-3 (a positive-sense 30-mer oligonucleotide corresponding to the leader sequence of JHMV) (20), and the reverse primer, S-stp-NdeI-N (5Ј-TTCATATGTGCCAACTTACTTGAGG-3Ј), corresponding to nucleotides 3909 to 3933 in the cl-2 S gene from the first nucleotide of the initiation codon (36).…”
mentioning
confidence: 99%
“…Thus, these CoVs fail to induce syncytia in infected cells, and the S protein on the virion is not in a cleaved form (4,27,41). However, those S proteins are cleaved by exogenous proteases, such as trypsin, into two subunits similar to MHV S1 and S2 (19,45,48), and this cleavage event leads to the activities of cell-to-cell and cell-to-virus fusion (18,36,41,48,49), although the efficiency of infection of those CoVs is not highly influenced by exogenous proteases (18,26,27). PEDV has uncleaved S protein (10), and PEDV-infected cells produce syncytia only after treatment with an exogenous protease, features similar to those of the CoVs described above.…”
mentioning
confidence: 99%
“…S protein also induces protection against mv and MHY. These proteins are frequently detected in small quantities in the surface of virus infected cells associated to the presence of virions, while they are detected in the cytoplasm of infected cells in large quantities29, 35,17,48,64,82,27,58,105,43,51,70,32,89,31,20,44,102,34. These data are in agreement with the concept that coronaviruses assemble at rough endoplasmic reticulum and Golgi membranes.…”
Section: Targets In Protectionmentioning
confidence: 99%